1994
DOI: 10.1016/0014-5793(94)00829-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of normal and abnormally phosphorylated tau in different cellular and regional compartments of Alzheimer disease and control brains

Abstract: Microtubule associated protein tau is abnormally phosphorylated in Alzheimer disease (AD) brain. In the present study we investigated (i) whether tau is axonal or both axonal and somatodendritic, (ii) whether tau is a marker of Alzheimer neurofibrillary pathology, and (iii) whether the levels of tau in the cytosol (100,000 x g supernate) from AD brain are altered. Frozen autopsied tissue from 20 AD, 17 normal aged and 15 neurological control cases obtained 3-8 h postmortem were analyzed. Levels of normal, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 26 publications
3
103
1
Order By: Relevance
“…Iron treatment to cultured neurons increases tau phosphorylation [153][154][155][156], so upstream iron elevation might increase pathological tau in AD. Total tau levels are also decreased in AD cortex [157][158][159][160], and we showed that loss of tau expression causes iron-and agedependent cognitive loss and cortical atrophy in mice [64]. Tau is required for APP trafficking to the neuronal membrane [64].…”
Section: Ironmentioning
confidence: 96%
“…Iron treatment to cultured neurons increases tau phosphorylation [153][154][155][156], so upstream iron elevation might increase pathological tau in AD. Total tau levels are also decreased in AD cortex [157][158][159][160], and we showed that loss of tau expression causes iron-and agedependent cognitive loss and cortical atrophy in mice [64]. Tau is required for APP trafficking to the neuronal membrane [64].…”
Section: Ironmentioning
confidence: 96%
“…Abnormal tau expression and hyperphosphorylation are common features in AD and DS (Khatoon et al, 1994;Oyama et al, 1994), causing abnormalities in the cytoskeleton. In addition, increases in tau expression have been reported in other mouse models of AD and aging (Manich et al, 2011;Doehner et al, 2010;Madhusudan et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…43,44,45 In tauopathies (such as AD and PD), insoluble tau aggregates are accompanied by a fall in soluble tau levels in affected tissue. 43,46,47,48,49,50,51 We have argued that this will lead to a loss of tau function that could cause neurodegeneration, as tau functions to lower neuronal iron levels by promoting the presentation of the amyloid protein precursor (APP) to the neuronal surface, 43 where it promotes the efflux of iron. 52,53,54 Without soluble tau, neurons accumulate iron to toxic levels, and hence tau-knockout mice develop a parkinsonism with impaired-cognition phenotype that is rescued by iron chelation.…”
Section: Introductionmentioning
confidence: 99%